Automotive Control Systems For Engine, Driveline, and Vehicle - Kiencke, Uwe; Nielsen, Lars (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Advances in automotive control systems continue to enhance safety and comfort and to reduce fuel consumption and emissions. Reflecting the trend to optimization through integrative approaches for engine, driveline and vehicle control, this book enables control engineers to understand engine and vehicle models necessary for controller design and also introduces mechanical engineers to vehicle-specific signal processing and automatic control. The emphasis on measurement, comparisons between performance and modelling, and realistic examples derive from the authors' industrial experience at Bosch and interactions within IFAC and SAE. The second edition offers new or expanded topics such as diesel-engine modelling, diagnosis and anti-jerking control, and vehicle modelling and parameter estimation. The book addresses professional engineers as well as students. With only a few exceptions, the approaches are close to those utilized in actual vehicles, rather than being purely theoretical.